New polyprenyl phosphate based preparation Fortepren® as promising cytokine regulationg antiviral remedy. (August 2016) - Pronin, Alexander V.; Narovlyansky, Alexander N.; Shulzhenko, Andrey E.; Sanin, Alexander V.; Sedov, Alexander M.
Graphical abstract: Highlights: Fortepren ® treatment led to increase of key cytokines taking part in the protection against virus infection. Abstract: Fortepren ®, a product of the phosphorylation of polyprenols from fir needles (with sodium polyprenyl phosphate being the main active ingredient), belongs to the class of antiviral drugs with immunomodulating activity. Fortepren ® may be used as the drug of choice in the treatment of herpes diseases. It was shown that treatment with Fortepren ® of patients with a chronic recurrent herpes infection after acute phase termination with acyclovir decreased the recurrence rate, as well as the severity of local symptoms. Fortepren ® treatment of patients with a high incidence of recurrent herpes infection led to an increase in the interferon-producing ability of leucocytes stimulated with NDV, as well as in the production of key cytokines (IL-1β, IL-15, MIP-1α, IFN-γ, IL-12 (p40), TNF-α, IFN-α2, IL-12 (p70), IL-6) taking part in the protection against viral infection. Data suggest that the action of the drug is directed, first of all, to the cells responsible for the natural resistance of the organism (macrophages, dendritic cells, etc.). The activation of natural immunity appears to be a leading mechanism of protection from herpesviral infection under the influence of polyprenyl phosphate.